Hepatoprotective properties of Penthorum chinense Pursh against carbon tetrachloride-induced acute liver injury in mice - Meng Wang; Xiao-Jiao Zhang; Ruibing Feng; Yun Jiang; Da-Yong Zhang; Chengwei He; Peng Li; Jian-Bo Wan (BMC, 2017)
Abstract Background Penthorum chinense Pursh (Penthoraceae, PCP), a well-known Miao ethnomedicine, has been traditionally used to treat several liver-related diseases, such as jaundice and viral hepatitis. The aims of the present study were to evaluate the probable properties of the aqueous extract of PCP on carbon tetrachloride (CCl4)-induced acute liver injury in mice. Methods C57BL/6 mice were orally administered an aqueous extract of PCP (5.15 and 10.3 g/kg BW) or silymarin (100 mg/kg) once daily for 1 week prior to CCl4 exposure. Silymarin serves as a positive drug to validate the effectivenes of PCP. Results A single dose of CCl4 exposure caused severe acute liver injury in mice, as evidenced by the elevated serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alanine phosphatase (ALP), and the increased TUNEL-positive cells in liver, which were remarkably ameliorated by the pretreatment of PCP. PCP was also found to decrease the levels of malondialdehyde (MDA), restore the glutathione (GSH) and enhance the activities of superoxide dismutase (SOD) and catalase (CAT) in the liver. In addition, the pretreatment of PCP inhibited the degradation of hepatic cytochrome P450 2E1 (CYP2E1), up-regulated the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and its target proteins in CCl4-treated mice. Conclusion Results indicated that the pretreatment of PCP (10.3 g/kg BW) effectively protected against CCl4-induced acute liver injury, which was comparable to efficacy of silymarin (100 mg/kg). This hepatoprotective effects might be attributed to amelioration of CCl4-induced oxidative stress via activating Nrf2 signaling pathway.